OPTIMISATION OF FLOW SHOP SCHEDULING PROBLEM: SIMULATION SYSTEM VS. EVOLUTIVE SOLVER - Kaczmar, Ireneusz; Bányai, Tamás (Advanced Logistic Systems - Theory and Practice, 2022)
In the Industry 4.0 era the optimisation of production processes become more and more important. A wide range of tools are used to improve the performance of production processes and related operations of the supply chain including purchasing, distribution and inverse processes. These tools have a great impact on the results of design and operation of production processes both technology and logistics point of view. Within the frame of this article, the authors are demonstrating the optimisation potentials of simulation tools and heuristic solvers (optimisers) through the problem of the well-knows permutation flow shop scheduling. They are describing the models and methods used in the case of FlexSim simulation systems and the heuristic solver option of Excel Solver. As the numerical results show, both the simulation model and the heuristic optimisation approach lead to a quasi-optimal solution.